2012
DOI: 10.1175/jas-d-11-0143.1
|View full text |Cite
|
Sign up to set email alerts
|

On Trade Wind Cumulus Cold Pools

Abstract: Shallow precipitating cumuli within the easterly trades were investigated using shipboard measurements, scanning radar data, and visible satellite imagery from 2 weeks in January 2005 of the Rain in Cumulus over the Ocean (RICO) experiment. Shipboard rainfall rates of up to 2 mm h 21 were recorded almost daily, if only for 10-30 min typically, almost always from clouds within mesoscale arcs. The precipitating cumuli, capable of reaching above 4 km, cooled surface air by 1-2 K, in all cases lowered surface spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
177
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(208 citation statements)
references
References 55 publications
19
177
1
Order By: Relevance
“…Within cold pools convection is suppressed, but at the downwind (colliding) boundaries of cold pools new convection can be triggered. This leads to arcshaped cloud formations with clear skies in between as seen from satellite imagery (Snodgrass et al 2009;Zuidema et al 2012), and which the LES reproduces. The cold pools from shallow cumuli and congestus are mostly dry in their center, similar to deep convection, because rain rates are sufficiently strong to bring down relatively dry air from higher altitudes.…”
Section: Large-eddy Simulationsmentioning
confidence: 84%
See 1 more Smart Citation
“…Within cold pools convection is suppressed, but at the downwind (colliding) boundaries of cold pools new convection can be triggered. This leads to arcshaped cloud formations with clear skies in between as seen from satellite imagery (Snodgrass et al 2009;Zuidema et al 2012), and which the LES reproduces. The cold pools from shallow cumuli and congestus are mostly dry in their center, similar to deep convection, because rain rates are sufficiently strong to bring down relatively dry air from higher altitudes.…”
Section: Large-eddy Simulationsmentioning
confidence: 84%
“…In these cells cloud droplets have been scavenged by drizzle drops, leading to very low cloud droplet number concentrations. Observations have also demonstrated that fields of shallow cumuli accompanied by significant rain are organized into arc-shaped formations (Snodgrass et al 2009;Zuidema et al 2012). These are representative for the presence of cold pools, which are produced by the evaporation of rain and convective downdrafts, similar to the cold pools that accompany deep convection (Tompkins 2001).…”
Section: Introductionmentioning
confidence: 95%
“…With the drop in temperature, there was a sharp spike in wind speed, relative humidity (and at times precipitation), as well as a drop in both particle concentration and water vapor mixing ratio. These characteristics are indicative cold pool events related to convective downdrafts (Wakimoto, 1985;Atkins and Wakimoto, 1991;Miller et al, 2008;Zuidema et al, 2012). Over 20 such events are observable in the time series, with significant variability in amplitude.…”
Section: High Frequency Squall Line and Cold Pools Phenomenonmentioning
confidence: 95%
“…Some previous studies have demonstrated clouds' alteration of their environment (Zhao and Austin, 2005;Heus and Jonker, 2008;Malkus, 1954;Lee et al, 2014;Zuidema et al, 2012;Roesner et al, 1990). One example of such an effect is the "preconditioning" or "cloud-deepening" effect (Nitta and Esbensen, 1974;Roesner et al, 1990;Stevens, 2007;Stevens and Seifert, 2008), where clouds cool and moisten the upper cloudy and inversion layers and in this way encourage the development of the next generation of clouds that encounter improved environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Another way clouds affect their environment is by the evaporation of rain below the cloud base, which induces cooling of the sub-cloud layer (Zuidema et al, 2012;Heiblum et al, 2016a). Lee et al (2014) demonstrated the aerosol effects on the field's CAPE (convective available potential energy) (as distributed above cloud base or below it).…”
Section: Introductionmentioning
confidence: 99%